2013
DOI: 10.1111/plb.12098
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity effects on different stages of higher plant life cycle and completion of the seed‐to‐seed cycle

Abstract: Human inhabitation of Space requires the efficient realisation of crop cultivation in bioregenerative life-support systems (BLSS). It is well known that plants can grow under Space conditions; however, perturbations of many biological phenomena have been highlighted due to the effect of altered gravity and its possible interactions with other factors. The mechanisms priming plant responses to Space factors, as well as the consequences of such alterations on crop productivity, have not been completely elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 62 publications
(120 reference statements)
3
40
0
Order By: Relevance
“…Any variations in growth parameters in Space-oriented ecologically closed systems can determine valuable changes in terms of optimisation of volume and resource recycling. These changes can be straightaway converted into economic saving or waste [9]. For example, the increase in the number and size of leaves induced in “Microtom” especially by low doses of irradiation can be beneficial to atmosphere regeneration of pressurised modules, provided that formed leaves do not show structural aberrations which reduce their function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any variations in growth parameters in Space-oriented ecologically closed systems can determine valuable changes in terms of optimisation of volume and resource recycling. These changes can be straightaway converted into economic saving or waste [9]. For example, the increase in the number and size of leaves induced in “Microtom” especially by low doses of irradiation can be beneficial to atmosphere regeneration of pressurised modules, provided that formed leaves do not show structural aberrations which reduce their function.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on Space exploration, there is common agreement that long-term human permanence in Space relies on the possibility to regenerate resources in Bioregenerative Life Support Systems (BLSSs) where plants can play a key role [6, 7]. Plant growth is not prevented in Space; however, although plants can be more resistant than other organisms to specific Space factors (including reduced gravity and cosmic radiation), there is also evidence of altered growth and reduced fitness [2, 8, 9]. Many studies have indicated the occurrence of either positive or negative phenomena in plants exposed to low-LET (linear energy transfer) (e.g., X- and gamma-rays) and high-LET (e.g., protons and heavy ions) ionising radiation [2].…”
Section: Introductionmentioning
confidence: 99%
“…New information and insights have been obtained with regard to both vegetative and reproductive growth (for review see e.g. Correll & Kiss 2008;Ferl et al 2002; see also De Micco et al 2014a;Ueda et al 2014). Major progress is coming from investigations of plant hormone signalling pathways, in particular those involved in IAA transport (Geisler et al 2014;Ueda et al 2014).…”
Section: Graviresponsesmentioning
confidence: 99%
“…Although we are aware that seed‐to‐seed cycles can be achieved, the review from De Micco et al . () highlights some negative effects of space conditions on plant growth and the consequences for crop productivity. Generally supporting this view, Paradiso et al .…”
mentioning
confidence: 99%